Dekonstruksi Derrida dan Metode Istiqra’ Al Ma’nawi Menurut Asy Syathibi dalam Memahami Teks Al Quran - Venny Delviany; Amril M; Eva Dewi (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
Derrida's Deconstruction and Imam Asy Syathibi's Istiqra al Ma'nawi Method are two methods that both study texts but have different objects. Derrida's deconstruction is a form of text interpretation that is carried out radically, bringing out elements that are contradictory to each other which results in a truth, while the istiqra al ma'nawi method of looking at studies of Islamic legal texts is by combining a number of other texts that contain different aspects and objectives. , so that a legal case is formed based on a combination of the text's arguments while still acting on reason, taking into account social conditions, as well as dimensions and places to realize the benefit of humanity from various aspects summarized in the principles of dharuriyah, hajiyah and tahsiniyah. Qualitative research data was obtained from official documents and websites and relevant literature reviews were then presented and analyzed. This study aims to find out whether Derrida's deconstruction is the same as Imam Asy Syathibi's Istiqra al Ma'nawi method in understanding the text of the Koran. This study finds that Derrida's deconstruction and the istiqra al Ma'nawi method conflict with the aim of istiqra al Ma'nawi itself, namely to seek legal certainty from texts with a method that adheres to the unity of the text, not the application of the text separately. Therefore, Derrida's deconstruction leaves the text ambiguous, providing multiple meanings and allowing the reader to speculate on meaning. This makes deconstruction not applicable and not the same in interpreting the texts of Islamic legal propositions using Imam Asy Syathibi's Istiqra al Ma'nawi method.